Technological Model Based on Artificial Intelligence for the Generation of Commercial Texts in Marketing Campaigns in Medical Clinics in the City of Huancayo - Picho Peña, Karen Lorena (2025)
This study presents a technological model based on artificial intelligence (AI) for the generation of commercial texts within marketing campaigns targeted at medical clinics in the city of Huancayo. The model aims to streamline and enhance the process of creating persuasive and informative content to effectively engage target audiences. By leveraging AI capabilities such as natural language processing and machine learning algorithms, the system autonomously generates compelling marketing texts that resonate with the specific needs and preferences of the local community in Huancayo. Through a combination of data analysis, linguistic patterns, and user feedback, the model continues to refine its production to optimize relevance and effectiveness. This innovative approach not only reduces the time and resources required for text generation but also ensures consistency and coherence across various marketing channels. The integration of AI technology enables medical clinics in Huancayo to establish a stronger digital presence, attract potential patients, and foster lasting relationships with existing clientele. In summary, this technological model represents a significant advancement in marketing strategies tailored to the healthcare sector in regional contexts such as that of Huancayo.